British Colonial Rule in Botswana and its Effects on Post-Independence Economy - BENKHELIFA, Imane; AFKIR , Mohamed (Journal of Social Sciences and Humanities, 2021)
Although Botswana was the third poorest country at independence in 1966, it experienced an astonishing rapid economic development and is often considered as an exceptional country among the African countries with regard to its economic success. Appropriate policies, effective political institutions, the discovery of diamonds, and good leadership all together contributed to this success. However, the nature of British colonial rule in Botswana and its eventual post-independence consequences is a crucial factor to explain the economic success. Therefore, this article aims to evaluate the British colonial rule and its impact on the future of Botswana's economy. This paper tends to emphasize the importance of being neglected in making minimal impact on Botswana after independence compared to other former colonies. Furthermore, the study examines the conditions that led Botswana to sustain spectacular post-independence development. The historical approach is the determinant method in this paper in which qualitative analytical and descriptive methods are used to examine the historical events of Botswana during the colonial period including applying the limbo approach, taxation system, maintaining pre-colonial institutions, the rise of nationalism and unity, male migration, and work in mining. The article draws the conclusion that British colonial rule had a positive impact on long-term economic development through three important factors. The first factor is the rise of Botswana unity. The second factor is the establishment of effective institutions. The third factor is the impact of taxation (cash-based economy, the modern wage labor sector more effective, and getting a great experience from mining in South Africa). Since much evidence supports that the key reason of Botswana's success is the strong government and the effective institutions, this article results in proving that The nature of British colonial rule in Botswana resulted in a political, economic, and social setting that could prepare a favorable ground for effective institutions to be adapted.